Assistive/Socially Assistive Robotic Platform for Therapy and Recovery: Patient Perspectives - Matthew White; Mary Vining Radomski; Marsha Finkelstein; Daniel Allan Samuel Nilsson; Lars Ingimar Eugen Oddsson (International Journal of Telemedicine and Applications)
Improving adherence to therapy is a critical component of advancing outcomes and reducing the cost of rehabilitation. A robotic platform was previously developed to explore how robotics could be applied to the social dimension of rehabilitation to improve adherence. This paper aims to report on feedback given by end users of the robotic platform as well as the practical applications that socially assistive robotics could have in the daily life activities of a patient. A group of 10 former and current patients interacted with the developed robotic platform during a simulated exercise session before taking an experience-based survey. A portion of these participants later provided verbal feedback as part of a focus group on the potential utility of such a platform. Identified applications included assistance with reaching exercise goals, managing to-do lists, and supporting participation in social and recreational activities. The study participants expressed that the personality characteristics of the robotic system should be adapted to individual preferences and that the assistance provided over time should align with the progress of their recovery. The results from this study are encouraging and will be useful for further development of socially assistive robotics.